NADH dehydrogenase as a molecular target for artemisinin related antimalarian drug screening in a yeast model / Ummul Hanan Mohamad - Mohamad, Ummul Hanan (Institute of Graduate Studies, UiTM, 2015)
Artemisinin is currently the only effective drug against malaria. However, artemisinin-resistant Plasmodium had begun to emerge in many malaria endemic areas. Discovery of new anti-malarial with artemisinin-like activity had been slow as the molecular target of artemisinin was yet to be established. In addition, studies on the malaria causative agent were also hampered because Plasmodium was difficult to culture in-vitro. Therefore, this research aims to develop a reliable yeast screening system to help clarify artemisinin mode of action as well as accelerate the discovery of potential anti-malaria with artemisinin-like properties. The NADH dehydrogenase enzyme, which was coded by NDE1 and NDI1, in Saccharomyces cerevisiae as thought to be a major molecular target for artemisinin. A yeast system was constructed in which the efflux pump regulator genes, PDR1 and PDR3, and either NDE1 or NDI1 were deleted. Absence of the PDR1 and PDR3 genes minimized the ability of yeast to remove the test drugs into the extracellular environment, thus the drug effect could be clearly observed…